Recovery of value added products of Sm and Co from waste SmCo magnet by hydrometallurgical route - Sinha, M.; Pramanik, S.; Kumari, A.; Sahu, S.; Prasad, L.; Jha, M.; Yoo, Kyoungkeun; Pandey, B. (Pergamon Press, 2017)
Recovery of value added products of samarium and cobalt from the waste SmCo magnet was carried out by leaching and solvent extraction. Prior to the leaching the magnet was demagnetized by roasting at 1123 K. Leaching of Sm and Co from the roasted SmCo magnet was optimized by varying different process parameters such as acid type, acid concentration, pulp density, stirring speed and temperature. Under the optimized conditions of 4 M HCl, 368 K, 100 g/L pulp density, 500 rpm almost complete leaching of Sm and Co was obtained. Mechanism of leaching was established by studying the kinetics and characterization of leached residue. Kinetic study shows that the leaching of Sm and Co in HCl from roasted SmCo magnet is chemically controlled and proceeds through the surface chemical reaction of the particles with the acid. Samarium and cobalt from the leach liquor were separated by solvent extraction with Cyanex 572 at the phase ratios of 2:1 in 2-stages and 1-stage, respectively. From the purified solutions of Sm and Co, Sm2(C2O4)3·10H2O and Co2C2O4·2H2O were prepared by treating with stoichiometric amounts of oxalic acid. Oxalates of Sm and Co were roasted at 1073 K and 673 K, respectively for 240 min to produce Sm2O3 and Co3O4. The oxides of Sm and Co were characterized by chemical analysis, XRD and SEM-EDS studies.